Economic and Social Impacts of Male Migration on Families Left-Behind (Global Journal of Human-Social Science, 2019)
Some of the major streams of temporary migrant workers come from Asian countries. Almost all these migration flows involve the division of migrants from their families. Consequently, transnational families in which one or more members are abroad for several years are increasingly common in the Asian region. Moreover, there is an increasing number of migrant families with one or both parents who are migrated overseas for work for a substantial part of their children's growth. While the issue of families and children left behind by migrant men has not yet been intensively studied and it remains underresearched and indeed little understood in Sri Lanka, which is one of the major suppliers of overseas domestic workers. Currently, the Sri Lankan government faces a dilemma. On one hand, remittances from overseas migrant workers are the second largest source of foreign export earnings. On the other hand, there is a growing concern with the social effects of that movement on the children and wives left behind by migrant men. So this study has identified the impacts of male migration on left-behind families. While, it is impossible to conclude that the effects of international male out migration are only positive or negative, social impact is greater than economic benefits, or economic benefits are greater than social costs since the study has found mixed results of positive impacts, as well as negative, social impacts.
Keywords: male migration; left-behind family; benefit; cost; impact